Hydrodynamic behaviour change at Rambai river outlet, Juru river basin, Penang - Edlic Sathiamurthy; Chan, Ngai Weng (Environmental Management Society, Malaysia, 2006)
Rambai Valley is a partially urbanized and flood prone coastal plain located in the State of Penang. The valley is drained by Rambai River and its tributaries. Rambai River water level flux is subjected to daily tidal oscillation as the river is connected to the sea through the Juru River. During heavy rainfall events, the interactions between tidal intrusion and peak-flows in this coastal floodplain caused floods to occur. Tidal intrusion prevents effective outflows resulting in the accumulation of water that results in severe flooding. As a result, several flood management measures have been taken to mitigate floods. One of the most significant structural measures undertaken was the modification of the Rambai River outlet. This outlet, originally a small culvert was replaced with a large open channel in early 2003. The effectiveness of the new open channel in flood mitigation is examined and evaluated. The results of this research found that the new open channel may not be an effective flood mitigation measure and it may even aggravate future floods